III National Congress of Geography, Bolivia 2022 - Machaca Mamani, Edwin (2022)
The events carried out to disseminate, socialize and show the scientific advances related to geography were given at the university from the year 1984, having registered the first two congresses carried out by the Geographic Engineering Career. The First National Meeting of Geography was held in 1995, almost two decades later, the II National Congress of Geography held in 2014. And the last event held in this administration 2022 called the III National Congress of Geography Bolivia, 2022, constituting itself as another of the events of national scope with the participation of high authorities of the university system as well-known personalities in the academic field and also the presence and participation of authorities of the Plurinational State of Bolivia, whose main purpose was to achieve a meeting between professional geographers, sharing the experiences of the exhibitors through the exhibitions of projects carried out in the field of geography, knowing the advances in technology with tools for its application and, most importantly, the contribution to the visualization of Geography in all latitudes of our country.